Respostas
respondido por:
2
12p+4q=5
3p-4q=0
15p+0=5
p=1/3
Agora substituindo o valor de p na equação:
3·(1/3) - 4q=0
1-4q=0
-4q=-1
q=1/4
3p-4q=0
15p+0=5
p=1/3
Agora substituindo o valor de p na equação:
3·(1/3) - 4q=0
1-4q=0
-4q=-1
q=1/4
respondido por:
1
3p-4q=0
3p=4q
p = 4/3 q
substituindo:
12*4/3q +4q =5
16q +4q =5
20q =5
q =5/20
p = 4/3*5/20 = 1/3
prova real :
3p-4q=0
3(1/3) - 4(5/20) =0
1 - 1 = 0
12p+4q=5
12(1/3) + 4( 5/20) = 5
4 +1 = 5
3p=4q
p = 4/3 q
substituindo:
12*4/3q +4q =5
16q +4q =5
20q =5
q =5/20
p = 4/3*5/20 = 1/3
prova real :
3p-4q=0
3(1/3) - 4(5/20) =0
1 - 1 = 0
12p+4q=5
12(1/3) + 4( 5/20) = 5
4 +1 = 5
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás